A new interactive approach for solving fully fuzzy mixed integer linear programming problems - Khalili, F.; Naseri, Seyed H.; Taghi-Nezhad, Nemat Allah (Yugoslav Journal of Operations Research; Vol 30 No 1 (2020), 2019)
Modeling and solving optimization problems is one of the most important issues in today environments. Fuzzy approach is used to overcome the vagueness, imprecision and uncertainty in real life situations. In this paper, we present a novel method to solve Fully Fuzzy Mixed Integer Linear Programming (FFMILP) problems. This method is based on the definition of membership function and using fuzzy interactive technique for solving the classical multi-objective programming. To illustrate the steps of the proposed method, numerical examples are solved and the answers are compared with other methods in the literature. Computational results present the application of the method.